AN ANALYSIS OF STUDENTS COMMUNICATION APPREHENSION IN SPEAKING CLASS - Hardiyanto, Asep (ETERNAL (English, Teaching, Learning, and Research Journal), 2022)
Speaking is one of the ways people communicate verbally. Important speaking skills, students must be able to speak English well. However, in reality students’ communication in speaking class often faces problems. One of them is communication apprehension, communication apprehension is people who feel bad feelings in communicative situations. Therefore, it is important to do further research through research to find out whether actually facing communication fears can help to succeed in learning to speak. Based on these problems, researchers are interested in examining the types and factors that cause student communication in the speaking class. This study aims to describe the types and factors that cause communication anxiety experienced by students. This study uses a descriptive approach. This research involved 7 participants from speaking class at Muhammadiyah University of Kotabumi. Data collection was done through a questionnaire with a google form. The results showed that students experienced network communication in types of traits such as, situational and general context. In this case, the person-group is the missing type in this study. Then for the anxiety factor, students experience novelty, formality, subordinate status, ignorance, inequality, attention, heredity and environment. The missing factors of Communication Aprehension are strengthening and defeating.